Using mock communities of arbuscular mycorrhizal fungi to evaluate fidelity associated with Illumina sequencing. (June 2018) - Egan, Cameron Patrick; Rummel, Alexii; Kokkoris, Vasilis; Klironomos, John; Lekberg, Ylva; Hart, Miranda
Abstract: Characterization of arbuscular mycorrhizal (AM) fungal communities increasingly relies on high throughput sequencing (HTS) datasets, but whether sequence data accurately depict AM fungal communities is unknown. We sequenced mock communities of 16 AM fungal morphospecies from six families that varied in relative abundance. To assess sequence variation within fungal individuals, we sequenced single spores of Rhizophagus irregularis . We observed that the relative abundance and taxonomic identity of operational taxonomic units (OTUs) within AM fungal families closely matched expected values, but this decreased at lower taxonomic levels. Multiple OTUs were observed within single spores, suggesting that using OTUs to estimate species richness may inflate richness estimates and reflect sequence variation within individuals. While HTS may introduce some bias in relative abundance estimates and taxonomic identification, we observed high consistency among replicate samples from the same mock community, indicating that these data can inform ecological patterns.